Islamic educational psychology, critical analysis study of Hamka and Zakiah Daradjat's thinking - Setiawan, Muhammad Nurrosyid Huda; Fadhlurrahman, Fadhlurrahman; Marzuki , Marzuki; Retnowati, Endah (Al-Misbah (Jurnal Islamic Studies), 2023)
This research focuses on a comparative analysis of Islamic psychology education from the perspective of two great figures, namely Hamka and Zakiah Daradjat. Islamic psychology is a field that explores the human mind and behavior through an Islamic lens, combining principles from the Koran and Hadith. Hamka and Zakiah Daradjat are figures who have made significant contributions in this field. By examining their approach to education, curriculum design, teaching methods, assessment practices, and their overall impact and influence, this research aims to provide valuable insights into the field of Islamic psychology education and its relevance today. The research method used is literature with interpretive data analysis methods, pragmatic and holistic content analysis. data validation using method triangulation and source triangulation. The results of this research focus specifically on the comparison of Hamka and Zakiah Daradjat in the context of Islamic psychology education. The scope includes their approach to education, curriculum design, teaching methods, assessment practices, and their overall impact on the field. This analysis will examine their individual contributions and highlight the similarities and differences between the two figures. In the theoretical study of these two figures, the results of educational approaches, curriculum design, teaching methods, assessment practices and their impact on the field emerge.